Differential Relationship between Microstructural Integrity in White Matter Tracts and Motor Recovery following Stroke Based on Brain-Derived Neurotrophic Factor Genotype - Eunhee Park; Jungsoo Lee; Won Hyuk Chang; Ahee Lee; Friedhelm C. Hummel; Yun-Hee Kim (Neural Plasticity)
Objective. The relationship between white matter integrity and the brain-derived neurotrophic factor (BDNF) genotype and its effects on motor recovery after stroke are poorly understood. We investigated the values of fractional anisotropy (FA) in the corticospinal tract (CST), the intrahemispheric connection from the primary motor cortex to the ventral premotor cortex (M1PMv), and the interhemispheric connection via the corpus callosum (CC) in patients with the BDNF genotype from the acute to the subacute phase after stroke. Methods. The Fugl-Meyer assessment, upper extremity (FMA-UE), and tract-related FA were assessed at 2 weeks (T1) and 3 months (T2) after stroke using diffusion tensor imaging (DTI). Fifty-eight patients diagnosed with ischemic stroke were classified according to the BDNF genotype into a Val (valine homozygotes) or Met (methionine heterozygotes and homozygotes) group. Results. The Val group exhibited a larger reduction of FA values in the ipsilesional M1PMv than the Met group from T1 to T2. The FMA-UE at T2 was negatively correlated with FA of the contralesional M1PMv at T2 in the Val group but was positively correlated with FA of the ipsilesional CST and CC at T2 in the Met group. Conclusions. The integrity of the intra- and interhemispheric connections might be related to different processes of motor recovery dependent on the BDNF genotype. Thus, the BDNF genotype may need to be considered as a factor influencing neuroplasticity and functional recovery in patients with stroke. This trial is registered with http://www.clinicaltrials.gov: NCT03647787.